Conversion of instable primary forests in the lusatian post-mining landscape - Ertle, Christoph; Bartelt, Daniel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the federal state Brandenburg in Germany about 464 000 ha of mainly middle aged Scots pine stands are planned to be converted. In addition, instable broad leaved forests like disintegrating monocultural birch and poplar stands on dumps of lignite mining need conversion. Forest owners feel unsure regarding the silvicultural treatment in these stands. Therefore, research is needed to develop strategies for a forest conversion practice in primary forests on dumps within the mining landscape.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); forest reclamation; forest conversion; under planting; height growth; mortality; vitality indicator